Production and Energy Partition of Lactating Dairy Goats Fed Rations Containing Date Fruit Waste - Endah Yuniarti; Dwierra Evvyernie; Dewi Apri Astuti (Faculty of Animal Science, Bogor Agricultural University, 2016)
Dates fruit waste (DFW) is a by-product of dates juice industry that contains high energy. So, it is suitable for an energy source in dairy goat ration. This study was conducted to observe the effect of DFW utilization in the ration on energy partition and productivity of lactating dairy goats. The experimental design was randomized block design using 9 primiparous lactating dairy goats. There were three types of ration as treatments used in this study, i.e. R0= 35% forage + 65% concentrate, R1= 35% forage + 55% concentrate + 10% DFW, and R2= 35% forage + 45% concentrate + 20% DFW. Data were analyzed using ANOVA and polynomial orthogonal test. The evaluated variables were dry matter intake (DMI), energy partition including energy intake, digestible and metabolizable energy, fecal and urine energy, energy in methane gas, and energy in milk, milk production and quality. The results showed that the linear decreased of DMI, energy intake, digestible energy, metabolizable energy, and urine energy with the increased of DFW level in the rations. The use of 10% DFW (R1) showed the lowest energy loss through feces and methane gas of all treatments about 1089.57 kcal/head/d and 2.36 kcal/head/d, respectively. The use of DFW did not affect energy retention in milk. The utilization of DFW in ration did not significantly prevent the decline of milk production and milk quality. It can be concluded that DFW can be used as an alternative feed for the lactating dairy goat up to 10% in the ration.